Potentializing Wellness through the Stories of Female Survivors and Descendants of Indian Residential School Survivors: A Grounded Theory Study - Stirbys, Cynthia Darlene (Université d'Ottawa / University of Ottawa, 2016)
The Indian residential school (IRS) system is part of Canada’s colonial history; an estimated 150,000 First Nations, Inuit, and Métis children attended IRS (Stout & Peters, 2011). Informed by Indigenous principles of respect, relevance, responsibility, reciprocity, and relationality (Deloria, 2004; Ermine 1995; Kirkness & Barnhardt, 2001; Wilson, 2008), this study uses classic grounded theory to explore how female IRS survivors or their female descendants are coping with the intergenerational transmission of trauma. Specifically, the general method of comparative analysis was used to generate theory and identify categories and conceptualizations. The emergent problem found that individual survivors and their descendants were dealing with kakwatakih-nipowatisiw, a Cree term used to identify learned colonial (sick) behaviours. These behaviours manifested first among the administrative staff of the schools, then eventually emerged as female generational violence between, for example, mothers and daughters. Indigenous women in this study aimed to resolve this, their ‘main concern’, in order to strengthen familial relations, especially between female family members. Analysis resulted in the identification of a theory derived from the social process of potentializing wellness, which was grounded in the real-world experiences of Indigenous women. Potentializing wellness involves three dimensions: building personal competencies, moral compassing, and fostering virtues. It was revealed that Indigenous women perceive the ongoing generational effects of IRS differently, and as a result, three behavioural typologies emerged: living the norm, between the norm, and escaping the norm. The “norm” refers to the belief that violence is accepted as a normal part of family life. The paradox, of course, is that this type of behaviour is not normal and Indigenous women in this study are looking for ways to eliminate aggressive behaviours between women. The discoveries made in this research, coupled with the final integrative literature review, suggest that Indigenous People’s cultural ways of knowing have a holistic component that addresses all wellness levels. Effective strategies to deal with intergenerational trauma can emerge when holistic health is followed by, or happens concordantly with, reclaiming cultural norms grounded in community and spiritual life. Indigenizing a Western intervention is not enough. Focusing on the spiritual as well as emotional, physical, intellectual, and social aspects of self is seemingly the best approach for Indigenous People who are dealing with the intergenerational effects of trauma.
Keywords: Indigenous women; Indian residential schools; historical trauma; gender; mental health; grounded theory; models of wellness; Indigenous ways of knowing; Two-eyed seeing